Forensics and ship logs solve a 200-year mystery about where the first kiwi specimen was collected - Scofield, Paul; De Pietri, Vanesa (New Zealand Science Review, 2021)
The following article is republished from The Conversation, dated 14 April 2021 (https://theconversation.com/forensics-and-ship-logs-solve-a-200-year-mystery-about-where-the-first-kiwi-specimen-was-collected-158410). As required in this journal’s republishing guidelines, the article has not been edited, but we have attributed the authors and their institute.